x + ay = b ax – by = c solve it by elimination method​

Question

x + ay = b

ax – by = c solve it by elimination method​

in progress 0
Autumn 1 month 2021-10-18T22:31:13+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-18T22:33:01+00:00

    x + ay = b – – – 1

    ax – by = c – – – 2

    Divide 2 by a

    We get,

    x – by/a = c/a – – – 3

    Subtract 3 from 1

    We get

    ay + by/a = b – c

    (a^2 y + by) /a = (b-c)

    a^2 y + by = a(b-c)

    y(a^2 +b) = a(b-c)

    y = a(b-c) /(a^2 +b)

    Put value of y in 1

    We get,

    x + a*a (b-c) /(a^2 +b) = b

    x = b – { a^2 (b-c) /(a^2 +b)}

    x = (a^2b + b^2) a^2 (b-c) /(a^2 + b)

    x = (a^2b + b^2 a^2b a^2c) /(a^2 +b)

    x = (b^2 a^2c) /(a^2 +b)

    0
    2021-10-18T22:33:02+00:00

    Step-by-step explanation:

    ______________

    I hope the above answer’ll help U mark him as brainliest✌✌

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )